Smoking Does Not Alter Treatment Effect of Intravenous Thrombolysis in Mild to Moderate Acute Ischemic Stroke—A Dutch String-of-Pearls Institute (PSI) Stroke Study - Kufner, Anna (Front Neurol, 2020)
Background: The smoking-thrombolysis paradox refers to a better outcome in smokers who suffer from acute ischemic stroke (AIS) following treatment with thrombolysis. However, studies on this subject have yielded contradictory results and an interaction analysis of exposure to smoking and thrombolysis in a large, multicenter database is lacking. Methods: Consecutive AIS patients admitted within 12 h of symptom onset between 2009 and 2014 from the prospective, multicenter stroke registry (Dutch String-of-Pearls Stroke Study) were included for this analysis. We performed a generalized linear model for functional outcome 3 months post-stroke depending on risk of the exposure variables (smoking yes/no, thrombolysis yes/no). The following confounders were adjusted for: age, smoking, hypertension, atrial fibrillation, diabetes mellitus, stroke severity, and stroke etiology. Results: Out of 468 patients, 30.6% (N = 143) were smokers and median baseline NIHSS was 3 (interquartile range 1–6). Smoking alone had a crude and adjusted relative risk (RR) of 0.99 (95% CI 0.89–1.10) and 0.96 (95% CI 0.86–1.01) for good outcome (modified Rankin Score ≤ 2), respectively. A combination of exposure variables (smoking and thrombolysis) did not change the results significantly [crude RR 0.87 (95% CI 0.74–1.03], adjusted RR 1.1 (95%CI 0.90–1.30)]. Smoking alone had an adjusted RR of 1.2 (95% CI 0.6–2.7) for recanalization following thrombolysis (N = 88). Conclusions: In patients with mild to moderate AIS admitted within 12 h of symptom onset, smoking did not modify treatment effect of thrombolysis.